Relationship Between Public Debt And Financial Development In Kenya - Kipyego, Samwel; Njoka, Charity; Muniu, Joseph (International Journal of Finance and Accounting, 2022)
Purpose: This study sought to analyze the relationship between public debt and financial development in Kenya. The specific objectives were to examine the association between public domestic debt and financial development, to analyze the connexion between public external debt and Kenya's financial development. The study was underpinned on Financial Repression, Financial Liberalization, Lazy Bank Hypothesis, Demand following hypothesis, and the MacKinnon theoretical model. Methodology: The study applied positivism philosophy and explanatory research design. The study used country data hence no need for sampling. Data was collected for 1964 to 2019 from Kenya's Central Bank. Descriptive and inferential statistics were used in the study. Diagnostic tests such as Multi-collinearity, Auto-correlation, Normality, and Unit root were performed. Specifically, the long-run and short-run relationships were analyzed using the Auto-Regressive Distributive lag (ARDL) bound test for cointegration. An error correction model was applied to examine the short-run association. Finding: The test suggested the presence of a stable long-run relationship between financial development, public domestic debt, public external debt, and interest rate. The study finding indicates that public domestic debt has a statistically significant negative relationship with Kenya's financial development both in the long and short run. Also, public external debt has a statistically significant positive long and short-run association with financial development. Unique Contribution to Theory, Practice and Policy: The affirms liberalization theory by Shaw and Mackinnon (1973), advocating for a reduction in direct government participation in the financial market credit restriction In addition the study's findings are consistent with the lazy bank hypothesis by Hauner (2009) In addition, the government must ensure appropriate market-determined interest rate must be applied in domestic public debt. Furthermore, the government should continue fostering financial liberalization policies that encourage public external debt has its impacts positively on financial development.